(untitled) (مجلة الواحات للبحوث والدراسات, 2017)
Appeal Judgment Rollsof ‘Ami:Sa’i:Dmosque Are Considered Authoritative Historical Resources In Studying Mzab Valley History, In Particular. They Provide Researchers With Rich Historical Material That Could Judge Historical Books Written About Mzab Valley. Moreover, They Furnish Researchers With Substantial Valuable Historical Material, Which, Perhaps, Is Missing In The Historical Books, Over Different Periods Of Time, Regarding A Variety Of Mzab Life Aspects. This Research Sheds Light On Administrative, Judicial And Social Aspectsthrough Terminology That Was Taken As A Sample Of The Following Research. Key Words- Appeal Judgment Rollsof ‘Ami:Sa’i:Dmosque